2016
DOI: 10.21315/jcdc2016.21.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Variation Orders on Time and Cost in Mega Hydropower Projects of Pakistan

Abstract: Abstract:The occurrence of variation orders (VOs) in the construction industry is a regular trend all over the world. Hydropower projects are no exception, and it is difficult to find a hydropower project in Pakistan that does not experience VOs. The current research investigates the causes and impacts of VOs in mega hydropower projects using case studies of three mega hydropower projects in Pakistan. The results illustrate that errors and omissions in design, changes in scope and changes in design were among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 13 publications
(15 reference statements)
0
17
0
Order By: Relevance
“…Many researchers have evaluated the causes of design changes based on the construction stages like pre-planning, planning, design and construction [34,36,37] whereas few researchers have categorized the sources of design change from the perspective of Clients, consultants and contractors [6,9,29]. The dynamics can be classified into internal and external factors which are adopted in this paper.…”
Section: Causes Of Design Changes Impacting the Cost Overrunmentioning
confidence: 99%
“…Many researchers have evaluated the causes of design changes based on the construction stages like pre-planning, planning, design and construction [34,36,37] whereas few researchers have categorized the sources of design change from the perspective of Clients, consultants and contractors [6,9,29]. The dynamics can be classified into internal and external factors which are adopted in this paper.…”
Section: Causes Of Design Changes Impacting the Cost Overrunmentioning
confidence: 99%
“…From the literature review, it is found that there are 18 main causes of the variation works identified by most researches ( [5], [6], [2], [7], [3], [8], [9], [10], [11], [12], [13], [14], [15], [16] and [17]). The causes of variation order are described as follows:…”
Section: The Causes Of Variation Workmentioning
confidence: 99%
“…The prediction of the production progress is sometimes problematic in on-site construction (Russel et al 2004). The unpredictability of task duration is caused by varying labor productivity, uncertainty in quality of estimates, and the possibility of changes during construction (Hanif et al 2016;Russel et al 2014;González et al 2010). Howick (2003) and Flyvberg et al (2009) have underlined that uncertainty in estimates have a huge impact on time-, cost-, and quality performance.…”
Section: Introductionmentioning
confidence: 99%